Zero Waste Business Model: Building A Regenerative Business Model Through Innovation and Collaboration - Goklas Siahaan; Pilifus Junianto; Andi Tenri Pada; Carolina F. Sembiring; Desideria Regina (International Journal of Science and Society, 2023)
Traditional public businesses often prioritize profit over other things. This often causes significant negative impacts on the environment and surrounding natural resources. One step to overcome this problem is through the Zero Waste Business Model. This research aims to see how regenerative business models can be implemented through innovation and collaboration. This research will be carried out using a descriptive qualitative approach. The data used in this research comes from the results of relevant previous studies and research. The results of this research highlight the importance of cross-sector collaboration in achieving zero waste and regenerative business goals, as well as the role of innovation in supporting change towards sustainable business. In addition, this research also identifies the obstacles faced in adopting sustainable business models, including policy and regulatory constraints as well as internal challenges within the organization.